MEKANISME PERTAHANAN DAN KONFLIK DALAM NOVEL LENTERA MUSTIKA KARYA NISAH HARON - Halifah, Nur (BAHASANTODEA, 2015)
Abstract The purpose of this research is to describe the mechanisms of self-defense and conflict in novel with the title of â€œLentera Mustikaâ€ wrote by Nisah Haron. In this novel the theory were used humanistic personality theory by Abraham Maslow and personality theory of psychoanalysis Sigmund Freud. This research conducted through qualitative or descriptif research by using textual approach, and literature technical. The interactive model of data analysis has done by Miles and Huberman. They were marking, classifying and summarizing all of it and the results of the analysis that is consistent with the theory of psychoanalysis Sigmund Freudâ€™s personality and humanistic personality theory of Abraham Maslow. The results showed that, first the inner conflict of Ainur Mustika as a character in this novel through her status as unmarried woman and proposed marriage by two mans Rozario and Zul Farhan. Second, the inner conflict sublimation attitude was reflected when Ainur Mustika begun her relationship with God. Third, the inner conflict rationalization attitude occured when Ainur mustika called by Syed A.H and her relationship with this man. Fourth, inner conflict aggression attitude envisagedÂ when Ainur Mustika ridiculed to Syed Amirul Hakim and the phone called from Syed Amirul Hakim. Fifth, inner conflict projection attitude was reflected when Syed A.H came in her life and she would like to forget about all of the memories with Syed Amirul Hakim. Sixth the inner conflict about diversion attitude occured when Ainur Mustika has pressured by three mans they are Rozario, Zul Farhan, and Syed A.H and thought about her departure to Shanghai and seventh the inner conflict apathy was reflected when Ainur MustikaÂ has a relathionship status with Syed A.H. Keywords: defense mechanism, conflict, Lentera Mustika.